Investigation of an Innovative Technique for R.C. Piles Reinforced by Geo-Synthetics Under Axial Load - Badawi, Mona I.; Awwad, Mahmuod; Roshdy, Mohab; El-Kasaby, El-Sayed A. (Salehan Institute of Higher Education, 2024)
The use of alternative reinforcement material to enhance the performance of the pile capacity has gained increasing interest in recent years. This study seeks to probe the improvement of the ultimate pile capacity, reduction the deformation, and the financial results of using alternative reinforcement material such as glass fiber-reinforced polymers (GFRP), geosynthetics geogrids, as well as a combination of geosynthetics geogrids and a central steel bar. Axial load investigations were conducted on circular piles with 150 mm diameter and 1050 mm height. The experimental results revealed an improvement in the axial capacity of up to 25.4% and an enhancement in performance represented in ductility. Furthermore, financial and weight comparisons showed a decrease in the cost by up to 15%. Moreover, a nonlinear finite element (FE) study with Abaqus software was employed to standardize the numerical outcomes with the laboratory findings. The FE analysis was also verified with the previous studies. The 3D nonlinear finite element numerical model performed showed convergence with and without representing the surrounding soil of the pile; thus, confirming the adequacy of the experimental setup adopted. Finally, a suggested theoretical equation is developed to evaluate the change in pile axial load capacity based on the use of different reinforcement materials. The application of the proposed theoretical equation provides further insight into the governing equation involving different reinforcing materials. Doi: 10.28991/CEJ-2024-010-10-011 Full Text: PDF